2007
DOI: 10.1021/bm070088+
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte-Mediated Adsorption of Amelogenin Monomers and Nanospheres Forming Mono- or Multilayers

Abstract: We have applied optical waveguide lightmode spectroscopy combined with streaming potential measurements and Fourier transformed infrared spectroscopy to investigate adsorption of amelogenin nanospheres onto polyelectrolytes. The long term objective was to better understand the chemical nature of these assemblies and to gain further insight into the molecular mechanisms involved during self-assembly. It was found that monolayers of monomers and negatively charged nanospheres of a recombinant amelogenin (rM179) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Hence, these collective findings suggest that hydrophobic interactions between amelogenins play an important role in amelogenin self-assembly. A similar conclusion was drawn from studies on the adsorption of recombinant full-length mouse amelogenin (rM179) onto positively charged polyelectrolyte films [60]. Given the fact that amelogenin primarily contains hydrophobic residues, it is reasonable that hydrophobic interactions represent an important factor with respect to the regulation of protein-protein interactions.…”
Section: Discussionmentioning
confidence: 57%
“…Hence, these collective findings suggest that hydrophobic interactions between amelogenins play an important role in amelogenin self-assembly. A similar conclusion was drawn from studies on the adsorption of recombinant full-length mouse amelogenin (rM179) onto positively charged polyelectrolyte films [60]. Given the fact that amelogenin primarily contains hydrophobic residues, it is reasonable that hydrophobic interactions represent an important factor with respect to the regulation of protein-protein interactions.…”
Section: Discussionmentioning
confidence: 57%
“…Recent combined small-angle X-ray scattering (SAXS) and dynamic light scattering (DLS) experiments have indicated that a certain ellipticity (with the aspect ratio in the range of 0.45℃0.5) may be attributed to amelogenin assemblies [39]. Limited proteolysis experiments and those based on polyelectrolyte multilayers have indicated that regions at both C- and N- termini are exposed on the surface of the nanospheres [40, 41]. Accordingly, the structure of amelogenin nanospheres is usually depicted as the one with both C- and N- terminal regions present at the nanosphere surface (Figure 5), with the hydrophilic C-terminal supposedly in contact with apatite [8].…”
Section: The Structure and Role Of Amelogeninmentioning
confidence: 99%
“…By applying the small-angle X-ray scattering (SAXS) technique a model of a dense hydrophobic core with a flexible hydrophilic region exposed on the surface of amelogenin molecules has also been proposed [120]. Further support for the notion that amelogenin nanospheres assemble to possess negatively charged surfaces was obtained by applying optical waveguide lightmode spectroscopy combined with streaming potential measurements [121]. Amelogenin nanospheres adsorbed on a positively charged polyeletrolyte multilayer film surface in a single monolayer while successive multilayer adsorption was possible using a cationic mediator.…”
Section: Amelogenin Self-assembly In Vitromentioning
confidence: 99%